THE RELATIONSHIP BETWEEN TEACHING AND RESEARCH.INCLUSION AND DEVELOPMENT OF RESEARCH IN THE DEPARTMENT OF BIOLOGY, FACULTY OF SCIENCES OF UNAM (AN EXPLANATORY MODEL). (Andamios, Revista de Investigación Social, 2008)
This article is the result of the study of the process of incorporating research in an institutional milieu originally devoted to teaching and how the relationship is between these two activities, converting the institution studied into a body which provides education through scientific research. The case of the Department of Biology, School of Sciences of UNAM. Research in this community has been implemented with the creation of thirty-nine laboratories, all of them designed to support teaching. The interest of the analysis is to try to explain that what happened in Department of biology from the mid-sixties (1964) is a significant achievement among academic institutions in Mexico and around the world. The theme was addressed through three analytical axes: discipline, institution and major. However the centerpiece was the discipline itself. Each of them worked throughout the history of the institution from 1915 to 1994. The paper analyzes the development of Biology through the process of institutionalization and corroborates under the proposed analytical framework, which is the discipline with its own mechanisms of evolution, which offers moments of connection between teaching and research and stages of separation of the two functions. The notion of discipline helped build the conjecture that what happened in the Department of Biology was part of the academic development (cognitive) of the area and that it was through the process of integration and diversification processes and that the two processes were consecutive. At the same time, it was understood that in the pursuit of both mechanisms, the disciplines evolved and assured continuity , beyond the influence of external factors and the rise of research in the international arena. These processes undoubtedly contribute but without proper disciplinary advances would not have resonance. We concluded that this could be a model for the interpretation of historical work of other institutions and disciplines. Furthermore, it underscores the idea that respect and understanding these processes is essential to enable the advancement of scientific development in our country.
Keywords: The link between teaching and research; Department of Biology; disciplinary development; institution and discipline